Evaluation of owners’ and veterinarians’ attitudes toward veterinarian dressing styles in a teaching hospital in Taiwan - Tzu-yun Teng, Kendy; Shiu, You-Jing; Wang, Shang-Lin (Scientific reports, 2025)
This study examined preferences for veterinarian dressing styles from both pet owners’ and veterinarians’ perspectives. A questionnaire was distributed to investigate the attitudes of pet owners and veterinarians toward six different dressing styles, four hairstyles, and nine appearance-related subjects toward both male and female veterinarians. A total of 211 pet owners and 92 veterinarians were included. Our results indicated that veterinarian dressing style affected the first impression of pet owners. Pet owners considered wearing a white coat or surgical scrubs an appropriate dressing style for veterinarians. While owners had no sex preference for veterinarians ( p < 0.001), they had different attitudes towards various hairstyle for female and male veterinarians. Although any hairstyle, except for a bald hairstyle, was regarded as appropriate for female veterinarians among owners, male veterinarians with short hairstyles were considered more appropriate than other hairstyles. Wearing glasses, a name tag, a stethoscope, a watch, or sneakers tended to leave a neutral or appropriate impression. Wearing an earring, necklace, ring, or tattoo was considered very inappropriate by some owners. Overall, the owners were stricter than the veterinarians on different hairstyles but more permissive on appearance-related subjects.